Annual report 2017: CGIAR Genebank Platform - CGIAR Genebank Platform (CGIAR Genebank Platform, 2018)
The activities of the Genebank Platform are targeted specically to bring about increased conservation and use of genetic resources with the aim of achieving CGIAR System Level Outcomes (Sub-IDO 4.4) and UN Sustainable Development Goals (Target 2.5). The 2017 Annual Report reflects on activities and achievements in 2017.